2019
DOI: 10.1259/bjr.20180484
|View full text |Cite
|
Sign up to set email alerts
|

Biological effects of static magnetic field exposure in the context of MR-guided radiotherapy

Abstract: Image-guided radiotherapy (IGRT) aims to minimise uncertainties in treatment delivery through the use of medical imaging at frequent intervals throughout the patient's treatment course. One recent IGRT development has been the integration of MRI with a radiotherapy treatment machine. 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 63 publications
0
25
0
Order By: Relevance
“…Having a low-cost robust screening system for PDAC radiotherapy screening is particularly important not only because radiation on PDAC has been understudied, but furthermore, due to the limited availability of preclinical (animal) facilities for standard radiotherapy screening and the complete lack of animal facilities to screen novel radiotherapy regimes. More specically, novel radiotherapy regimes, e.g., with protons or in the presence of high magnetic elds as with MRI-linear accelerators, [98][99][100] are generally understudied and, considering the output of the ESPAC trial and others for PDAC (see above), novel radiation approaches could be more efficient. Indeed, there are some clinical trials on proton therapy which show promising results for PDAC.…”
Section: Radiotherapy Treatment In the Scaffoldsmentioning
confidence: 99%
“…Having a low-cost robust screening system for PDAC radiotherapy screening is particularly important not only because radiation on PDAC has been understudied, but furthermore, due to the limited availability of preclinical (animal) facilities for standard radiotherapy screening and the complete lack of animal facilities to screen novel radiotherapy regimes. More specically, novel radiotherapy regimes, e.g., with protons or in the presence of high magnetic elds as with MRI-linear accelerators, [98][99][100] are generally understudied and, considering the output of the ESPAC trial and others for PDAC (see above), novel radiation approaches could be more efficient. Indeed, there are some clinical trials on proton therapy which show promising results for PDAC.…”
Section: Radiotherapy Treatment In the Scaffoldsmentioning
confidence: 99%
“…Patients undergoing PET/MRI examinations are continuously exposed to both agents over a longer period. Moreover, various cell and animal studies found that SMF in combination with ionising radiation produces a significantly different outcome compared with ionising radiation alone [13]. Since synergisms were observed even when the SMF was applied before or after irradiation, changes of the dose distribution by SMFs can likely be excluded as a relevant interaction mechanism [13], as supported by Monte Carlo simulations [14,15].…”
Section: Introductionmentioning
confidence: 93%
“…Moreover, various cell and animal studies found that SMF in combination with ionising radiation produces a significantly different outcome compared with ionising radiation alone [13]. Since synergisms were observed even when the SMF was applied before or after irradiation, changes of the dose distribution by SMFs can likely be excluded as a relevant interaction mechanism [13], as supported by Monte Carlo simulations [14,15]. A recent review on combined effects of the two agents [13] concluded that the current evidence is insufficient to identify the underlying mechanism(s) of the observed synergisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a considerable number of monographs [1][2][3] and papers [4][5][6][7][8][9][10][11][12] characterizing the effects of all kinds of magnetic field upon flora and fauna. Currently, a focus is noted on the effect of magnetic resonance imaging on humans [13][14][15][16] . There are several reports with well documented biological effects of magnetic field.…”
Section: Introductionmentioning
confidence: 99%